Next-Generation Sequencing (NGS) in Hematologic Diagnostics - Mehboob, Riffat (Pakistan Journal of Health Sciences, 2024)
Next-Generation Sequencing (NGS) has played a vital role in eld of medical diagnostics by providing insights into the genetic causes of various disorders. NGS enables the study of multiple genes linked to hematologic diseases simultaneously and is especially helpful in the diagnosis of complicated diseases such as lymphomas, leukemias and myelodysplastic syndromes [1]. NGS helps classify subtypes by detecting particular genetic changes, which is important for implementing the best treatment plans. NGS integration into hematologic diagnostics improves patient care by using high-resolution data and increasing diagnosis accuracy. This is especially crucial for conditions where the clinical symptoms are similar. NGS-based genetic pro ling aids in the prediction of patient outcomes and the course of disease, enabling more informed clinical decisions. Targeted therapy development is made possible by NGS, which also minimizes side effects and maximizes therapeutic e cacy. Despite its potential, the adoption of NGS faces several challenges including cost and accessibility, technical expertise and regulatory and ethical considerations. These di culties do, however, also provide opportunities: a broader use of NGS might greatly enhance diagnostic capacities and raise the standard of healthcare provided worldwide. International research projects that concentrate on the genetic components of hematologic illnesses can advance medical understanding worldwide and lead to novel therapeutic approaches. Global rates of morbidity and death can be decreased by better managing hematologic illnesses by early and precise diagnosis made possible by NGS. Globally, next-generation sequencing has great potential to improve hematopoietic diagnosis and patient care. Unlocking this technology’s full potential will require addressing its cost, accessibility, and technical expertise limitations. Integrating NGS into routine diagnostics could revolutionize the treatment of hematologic illnesses and improve patient outcomes and prospects globally as the world’s healthcare infrastructure develops